2020
DOI: 10.1111/and.13584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on sperm quality, lipid profile, antioxidant activity and histopathological changes in streptozotocin‐induced diabetes in rats

Abstract: In this study, the effect of low‐dose curcumin on sperm parameters, reproductive hormones, lipid profile, biochemical antioxidant parameters and the histopathological structure of the testis in diabetic male rats were evaluated. In the study, 28 male Wistar albino rats weighing 300–370 g and aged 8–10 weeks were used. Four groups of equal numbers have been created. Diabetes mellitus was induced with 45 mg/kg streptozotocin (STZ) in seven rats. Curcumin was administered to the rats in curcumin and the diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
5
12
0
Order By: Relevance
“…So, increased ROS levels decrease sperm motility and fertility (Aitken et al, 2014). Many scientific studies reported that DM decreased sperm motility significantly (Al-Oanzi, 2019; Belhan et al, 2020;Samadian et al, 2019). In our study, the results indicated that the sperm motility significantly decreased in the DM group compared to the control group.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…So, increased ROS levels decrease sperm motility and fertility (Aitken et al, 2014). Many scientific studies reported that DM decreased sperm motility significantly (Al-Oanzi, 2019; Belhan et al, 2020;Samadian et al, 2019). In our study, the results indicated that the sperm motility significantly decreased in the DM group compared to the control group.…”
Section: Discussionsupporting
confidence: 57%
“…Also, an increase in oxidative stress appears in diabetic patients caused by hyperglycemia (Long et al, 2015). Increased ROS levels also cause damage to various organs such as the heart, kidney, and testis (Belhan et al, 2020;Kandemir et al, 2018;Rosano et al, 2017) in diabetic patients. In an experimental study, it was reported that DM significantly decreased in vivo fertility rates (Scarano et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemia disrupts the synthesis of adenosine triphosphate and increases the production of ROS in the mitochondria, probably leading to decreased sperm viability and sperm motility, and other functional disorders [47]. In the current study, we observed an increased MDA level in the STZ-induced diabetic rats and decreased GSH and CAT levels, which are in agreement with the previous findings associated with oxidative stress in DM [48,49]. It has been previously reported that cordycepin increased the SOD, CAT, GPx, GR, GST, and GSH activities, while it decreased the lipid peroxidation in aged rats [50].…”
Section: Discussionsupporting
confidence: 92%
“…First of all, we found that sperm count, viability and motility decreased, and abnormal sperm count increased in the Mets group. Previous studies in obesity and diabetes mellitus are consistent with our findings (Belhan et al 2020, Jia et al 2018) and a recently human study firmly established that MetS and its components exhibited deleterious effects on semen quality (Chen et al 2020).…”
Section: Discussionsupporting
confidence: 92%